2010
DOI: 10.1182/blood-2010-01-262071
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent expression signatures of cytokines and chemokines are present and are independently prognostic in acute myelogenous leukemia and myelodysplasia

Abstract: The role of circulating cytokines and chemokines (C&Ckine) in activating signal transduction in leukemic cells is incompletely defined. We hypothesized that comprehensive profiling of C&Ckine expression in leukemia would provide greater insight compared with individual analyses. We used multiplex array technology to simultaneously measure the level of 27 C&Ckines in serum from 176 acute myelogenous leukemia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
155
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(169 citation statements)
references
References 46 publications
13
155
1
Order By: Relevance
“…36 Although we are unable to draw mechanistic conclusions, we observed that patients exposed to this regimen experienced significant increas in specific bone marrow cytokines, including those involved in differentiation (macrophage colony-stimulating factor and granulocyte colony-stimulating factor) and hematopoiesis stem cell factor. In patients who received induction chemotherapy, high expression of macrophage colony-stimulating factor-receptor and granulocyte colony-stimulating factor-receptor and low expression of stem cell factor-receptor have been shown to correlate with a better prognosis.…”
Section: Discussionmentioning
confidence: 63%
“…36 Although we are unable to draw mechanistic conclusions, we observed that patients exposed to this regimen experienced significant increas in specific bone marrow cytokines, including those involved in differentiation (macrophage colony-stimulating factor and granulocyte colony-stimulating factor) and hematopoiesis stem cell factor. In patients who received induction chemotherapy, high expression of macrophage colony-stimulating factor-receptor and granulocyte colony-stimulating factor-receptor and low expression of stem cell factor-receptor have been shown to correlate with a better prognosis.…”
Section: Discussionmentioning
confidence: 63%
“…9 Previous reports showed that serum levels of inflammatory cytokines or chemokines in AML patients may represent a prognostic factor and correlate with the clinical outcome. 10,11 In this context, we have previously shown that IL-8 may accelerate in vitro CD34 + cell differentiation towards CD161 + CD56 + (NK) cells, thus suggesting that cytokines or chemokines, released during an inflammatory process, may influence NK-cell differentiation. 4 In the present study, in order to address the question as to whether AML blasts may affect NK-cell development, we performed co-cultures of umbilical cord blood (UCB)-CD34 + cells in the absence [control (CTR)] or in the presence of fresh leukemia blasts belonging to different FAB categories.…”
Section: -5mentioning
confidence: 99%
“…The knowledge gained from multi-analytical determination of cytokines and adhesion molecules could allow better diagnosis and management of hematological malignancies, since cytokines or their receptors may also represent a target for specific anticancer therapy at the molecular level. Recently, some studies reported the possible diagnostic and prognostic use of cytokine levels in newly diagnosed AML and myelodysplastic syndromes [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%